2011
DOI: 10.1136/bmjqs.2009.035881
|View full text |Cite
|
Sign up to set email alerts
|

Displaying random variation in comparing hospital performance

Abstract: Despite statistically significant differences between hospitals, random variation is a crucial factor that must be taken into account when judging individual hospitals. The funnel plot provides easily interpretable information on hospital performance, including the influence of random variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
0
24
1
1
Order By: Relevance
“…Van Dishoeck et al 9 visualised uncertainty in differences between the quality of cardiovascular care in hospitals using three graphical techniques and concluded that random variation is a crucial factor that must be taken into account when judging individual hospitals. Hernandez et al 18 noted poor agreement between different methods of ranking hospital-based quality of care for heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Van Dishoeck et al 9 visualised uncertainty in differences between the quality of cardiovascular care in hospitals using three graphical techniques and concluded that random variation is a crucial factor that must be taken into account when judging individual hospitals. Hernandez et al 18 noted poor agreement between different methods of ranking hospital-based quality of care for heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the quality indicators was based on three criteria [14]: feasibility [15], discriminability [16,17], and statistical uncertainty [15,18,19]. As no previous studies report thresholds on these criteria, we set a priori thresholds based on consensus.…”
Section: Validation Of the Quality Indicatorsmentioning
confidence: 99%
“…The preset PMR sample size, regardless of the hospital's volume of activity, might introduce a bias. The bias and likelihood of an erroneous classification were limited by combining two approaches: (1) by introducing uncertainty (Van Dishoeck et al recently showed how, depending upon the method used, account can be taken of uncertainty 27 ) and (2) by comparing three categories of hospitals rather than individual hospitals. A second limitation concerns the quality of the data in the PMR sample.…”
Section: Limitationsmentioning
confidence: 99%